2022
DOI: 10.1021/jacs.2c00777
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Inductor

Abstract: A multitude of chemical, biological, and material systems present an inductive behavior that is not electromagnetic in origin. Here, it is termed a chemical inductor. We show that the structure of the chemical inductor consists of a twodimensional system that couples a fast conduction mode and a slowing down element. Therefore, it is generally defined in dynamical terms rather than by a specific physicochemical mechanism. The chemical inductor produces many familiar features in electrochemical reactions, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
135
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 76 publications
(145 citation statements)
references
References 107 publications
10
135
0
Order By: Relevance
“…These processes explain the occurrence of inductive effect in the low part of spectrum for LFP inside miscibility gap. This observation can also be confirmed by the fact that system of equations 9 and 10 satisfy mathematical condition for chemical inductor postulated in [12] for lithiation levels within the miscibility gap.…”
supporting
confidence: 53%
See 4 more Smart Citations
“…These processes explain the occurrence of inductive effect in the low part of spectrum for LFP inside miscibility gap. This observation can also be confirmed by the fact that system of equations 9 and 10 satisfy mathematical condition for chemical inductor postulated in [12] for lithiation levels within the miscibility gap.…”
supporting
confidence: 53%
“…Klotz et al [6] reviewed published experiments that observed inductive effects in low frequency part of EIS spectrum, summarizing two possible explanations that were prior given by [10,11] and proposed a plausible empirical equivalent circuit model. Very recently it was proposed [12] that chemical behaviour can also induce inductive effect if a system couples a fast conduction mode and a slowing down element. Based on this finding, authors of [12] provide a generalised description of a generic system that exhibits chemical capacitance in a low frequency part of spectra.…”
mentioning
confidence: 99%
See 3 more Smart Citations